2014
DOI: 10.1159/000365483
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Effects of Mesenchymal Stem Cells-Conditioned Medium on Microglial Cytokines Expression and Nitric Oxide Production

Abstract: Background/Aim: Microglia, the resident macrophages in the central nervous system, secrete various proinflammatory cytokines and undergo proliferation upon activation in various neurodegenerative diseases. Activation of microglia has been implicated in exacerbation of various neurodegenerative diseases. Recently, it has been proposed that mesenchymal stem cells (MSC) have immunosuppressive properties and the potential to moderate inflammation. This study aimed to elucidate the effects of MSC-conditioned medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…In addition to their differentiation capacity, ADSCs secrete many trophic factors and immunosuppressive molecules (Donega et al, ; Wang et al, ; Whone, Kemp, Sun, Wilkins, & Scolding, ). Therefore, the therapeutic capacity and the ability of ADSCs to repair injured tissue is likely the result of both cell differentiation and paracrine alone or in combination (Kim, Park, & Sung, ; Ooi, Dheen, & Tay, ; Whone et al, ). Also, it is important to know if all tissues behave the same when they receive implants of SCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their differentiation capacity, ADSCs secrete many trophic factors and immunosuppressive molecules (Donega et al, ; Wang et al, ; Whone, Kemp, Sun, Wilkins, & Scolding, ). Therefore, the therapeutic capacity and the ability of ADSCs to repair injured tissue is likely the result of both cell differentiation and paracrine alone or in combination (Kim, Park, & Sung, ; Ooi, Dheen, & Tay, ; Whone et al, ). Also, it is important to know if all tissues behave the same when they receive implants of SCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that MSCs from bone marrow are able to exert inhibitory effects toward microglia cells [41,55,[62][63][64]. Indeed, it was shown that the CM from rat bone marrow MSC was able to significantly inhibit the LPSinduced microglia proliferation, maintain the resting phenotype, and control markedly by suppressing major microglia functions, such as the phagocytic activity and cytokine production [55].…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, safety and efficacy of implanted ADSCs have been investigated in different animal models, and promising preclinical studies with good perspectives for translational approaches are underway. Increasing evidence in animal models of stroke [36,37], traumatic brain injury [38] and spinal cord injury [39], demonstrates that ADSCs play a crucial role in the repair of CNS damage, by stimulating neurogenesis and exerting neuroprotective effects [40,41]. A growing body of evidence indicates the potential therapeutic capacity of ADSCs in a variety of diseases as amyotrophic lateral sclerosis, Parkinson's disease, autoimmune diseases, and multiple sclerosis, highlighting the ability of ADSCs to reduce inflammatory states and induce beneficial effects [42].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), a subset of nonhematopoietic cells, possess pluripotent features and can be obtained from different sources such as bone marrow, umbilical cord, umbilical cord blood and adipose tissue of the human body. [2][3][4][5] They represent an advantageous cell type for cell-based therapies, due to their multi-lineage differentiation potential, [6][7][8] immunosuppressive activities owing to their paracrine effects and interaction with different immune cells, [9][10][11][12] and limited immunogenicity with low human leukocyte antigen (HLA)-I and no HLA-II expression. 13 These properties of MSCs have offered a new strategy in treatment of numerous autoimmune inflammatory diseases and have demonstrated promising results in safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%